Masyarakat Ekonomi Asean (MEA) dan Tinjauan dari Perspektif Ekonomi Syariah - Boy Syamsul Bakhri (UIR Press, 2015)
Masyarakat Ekonomi ASEAN (MEA) akan mengubah ASEAN menjadi kawasan dengan pergerakan bebas barang, jasa, investasi, tenaga kerja terampil, dan arus modal yang bebas. Masyarakat Ekonomi ASEAN akan menjadi kekuatan pendorong integrasi ekonomi di negara-negara ASEAN, dan antara negara-negara ASEAN dan seluruh dunia. Banyak yang percaya integrasi ekonomi akan mewujudkan kerangka ASEAN sebagai pasar tunggal dan basis produksi, untuk meningkatkan daya saing ekonomi nasional dan kawasan, untuk mendukung pembangunan ekonomi yang lebih merata, dan sebagai batu loncatan menuju integrasi penuh ke dalam ekonomi global. Komitmen implementasi blueprint AEC oleh negara-negara anggota ASEAN dan para pemangku kepentingan ekonomi syariah akan menjadi peran penting untuk mencapai tujuan Visi, Misi, dan Target ASEAN. The ASEAN Economic Community (AEC) will transform ASEAN into a region with free movement of goods, services, investment, skilled labor, and free flow of capital. ASEAN Economic Community will be the driving force of economic integration within ASEAN countries, and between ASEAN countries and the rest of the world. Many believe the economic integration will realize the ASEAN framework as a single market and production base, to increase competitive economic national and region, to support more equitable economic development, and as a stepping stone toward full integration into the global economy. Commitments of the implementation of AEC Blueprint by ASEAN member countries and the sharia economic stakeholders will be a crucial role to achieve the objective of the ASEAN Vision, Mission, and Targets.